POTENSI KARBON DI ATAS PERMUKAAN TANAH DI BLOK PERLINDUNGAN TAMAN WISATA ALAM GUNUNG BAUNG PASURUAN – JAWA TIMUR - Mohammad Chanan (Jurnal Gamma, 2011)
Mohammad ChananStaf Pengajar Jurusan Kehutanan, Fakultas Pertanian Peternakan, Universitas Muhammadiyah MalangAlamat Korespondensi : Pondok Blimbing Indah B7/6 MalangTelpon : 0341-473887, Hp : 08123317215, Email: chanan@umm.ac.idABSTRACTThe research aimed to assess the potential of carbon placed on land surface, exactly in standingplants, lower plants and necromass in protection blok of “Gunung Baung” Natural Tourism ParkPasuruan. Data collection was done by collecting primary data, or direct data taken from the fieldwhich would be calculated in alometric equation. Measurement in big plot with 20m x 100m dimensionor 2000m2 to measure trees with >30 cm diameter, sub plot with dimension 5m x 40m or 200m² tomeasure tree with size 5- 30 cm, 6 plot measured 0,5m x 0,5m or 0.25m to measure understory(understory), and necro-mass in box 20m x 100m or 2000m² for necro-mass with size >30 cm,necro-mass 5m x 40m or 200m² for necro-mass with size <5 cm. From the research done in“Gunung Baung” Natural Tourism Park Pasuruan assessed biomass stock on the land surface. Theywere wood biomass ± 9.196,4 understory ± 556,77 and necro-mass ± 271,46. so the total assessmentof biomass was ± 10.024,63 Mg ha ¹ with width 195,5 ha, carbon (C) amount was ± 4.611.32 Mgha ¹, and carbon dioxyde (CO2) 17.338,56 Mg ha ¹ or 17.338,56 Ton. Carbon assessment in “GunungBaung” Natural Tourism Park Pasuruan conservation blok was ± 4.611,32 Mg ha ¹ or 4.611,32 ton,vegetation in “Gunung Baung” Natural Tourism Park area had large carbon absorption with value ±17.338,56 Mg ha ¹ or 17.338,56 ton with width 138,5 ha area. There suggested further research ofcarbon assessment in limited usage for 20 ha, intensive usage blok 10 ha, and rehabilitation blokwith 27 ha width completing data of carbon assessment in “Gunung Baung” Natural Tourism Park.There needed socialization to the society around “Gunung Baung” Natural Tourism Park area aboutthe importance of forest as carbon savings and forest as toxic absorption element like carbondioxyde (CO2), methane (CH4), and nitrous oxyde (N2O) to decrease quality and contaminate airand environmentKeywords: Carbon, “Gunung Baung” Natural Tourism Park.